Factors that influence outcomes and device use for pediatric cochlear implant recipients with unilateral hearing loss - Park, Lisa R.; Gagnon, Erika B.; Dillon, Margaret T. (Frontiers in Human Neuroscience, 2023)
Introduction: Candidacy criteria for cochlear implantation in the United States has expanded to include children with single-sided deafness (SSD) who are at least 5 years of age. There are few studies that include daily device use as a factor influencing performance in pediatric CI recipients with SSD. The aim of this study was to investigate factors that impact outcomes in this population. A secondary aim was to identify factors that impact their daily device use. Methods: A clinical database query revealed 97 pediatric CI recipients with SSD who underwent implantation between 2014-2022 and had datalog records. The clinical test battery included speech recognition assessment for the CI-alone and spatial release from masking (SRM) results obtained with the CI and better ear combined. Linear mixed-effects models evaluated the influence of time-related factors on performance. A separate linear mixed-effects model evaluated factors influencing HHP. Results: Longer time since activation, shorter duration of deafness, and higher HHP were significantly correlated with better CNC word scores. Younger age at device activation was not found to be a significant predictor of CNC outcomes. There was a significant relationship between HHP and SRM, with children who had higher HHP experiencing greater SRM. There was a significant negative correlation between time since activation and age at test with HHP. Conclusions: The data presented here do not support a cut-off age or duration of deafness for pediatric cochlear implantation in cases of SSD. Instead, they expand on our understanding of the benefits of CI use in this population by reviewing the factors that influence outcomes in this growing patient population. Higher HHP, or greater percentage of time spent each day using bilateral input, was associated with better outcomes in the CI-alone and in the combined condition. Younger children and those within the first months of use had higher HHP. Clinicians should discuss these factors and how they may influence CI outcomes with potential candidates with SSD and their families. Ongoing work is investigating the long-term outcomes in this patient population, including whether increasing HHP after a period of limited CI use results in improved outcomes.